Pengaruh Servqual terhadap Kepuasan Pelanggan dengan Customer Experience sebagai Variabel Intervening pada Bioskop Cinepolis Bandung - Hardiansyah, Muhamad Arya; Oesman, Ida Farida; Prasetiyo, Wildan Guretno (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Quality of service has a significant impact on how customers perceive a business and how satisfied they are with that business overall, and the film industry is no exception. It is more crucial than ever for companies to provide outstanding service and satisfy consumers in the increasingly competitive entertainment industry. The goal of this study is to use customer experience as a prism through which to analyze Cinepolis Cinema Bandung's service quality (Servqual) and its connection to customer happiness. For its quantitative analysis, this study relies on survey techniques. After collecting data from 370 Cinepolis Cinema Bandung patrons, we used route analysis to search for indirect as well as direct correlations between variables. The research found that customer satisfaction and overall experience are significantly influenced by service quality. The relationship between service quality and contentment may be mediated via customer experience, which has direct and indirect effects on customer satisfaction, according to study. Based on these results, it seems that raising the bar for service quality may boost customer happiness by bettering the customer experience. Cinepolis Cinema Bandung's management is urged to enhance customer satisfaction and competitiveness by consistently enhancing service quality parameters and focusing on providing unique customer experiences.